Effectiveness of Asynchronous Teaching Learning Approach to 4th Year BSHM Students at BCP A.Y. 2021-2022: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Online learning tools have recently been a hot topic in the educational and research literature, particularly at the university level. Various college administrators are putting a lot of emphasis on online education as a valuable teaching tool. These online learning materials have been demonstrated to make educational opportunities available to the greatest number of students at any time and in any location. Online resources are currently regarded as a technique for enhancing education, increasing learners' access to learning, and lowering instructional expenses. Distance education is increasingly filling a need for educational options that transcend geographic, time, and resource constraints. It is now necessary to retool and refocus oneself to remain relevant. As a result, an increasing number of people are looking for ways to educate themselves, and distance education has created a feasible choice for achieving educational goals with minimal compromise. This research focuses on the effectiveness of the asynchronous teaching-learning approach to 4th-year BSHM students at BCP. This research utilized the descriptive method using a quantitative approach to gather information about the effectiveness of the asynchronous teaching-learning approach to 4th-year BSHM students at BCP A.Y. 2021-2022. The respondents of this quantitative research are the one hundred (100) 4th-year students of the Bachelor of Science in Hospitality Management of Bestlink College of the Philippines. Despite the pandemic, asynchronous learning at BCP is ineffective because of the numerous elements that influence students' learning during the phase of the pandemic. It reduces the quality of the learning experience, causes learning resource challenges, limited interactions, and distraction, and affects one's health in emotionally disconnected and demotivated. Based on the gathered data and conclusions drawn, the administration and lecturers should respond to students' concerns based on the data obtained and conclusions reached. They should create a productive learning environment by creating a plan to complete and evaluate the work assigned, participate in virtual interactions with peers, and fully participate in an online class. Management, schools, and academics who employ asynchronous methods should develop engaging asynchronous techniques based on the ideas in this study.